2017
DOI: 10.1177/1527476417697270
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Public Issues in Romanian Broadcast Talk: Personalized Communication Strategies

Abstract: The article examines emerging practices of personalization in political talk shows on Romanian television. Our interest lies in the reconfiguration of the role of critical journalist, as performed by talk show hosts on private TV channels, in the context of increasing commercialization and instrumentalization of the Romanian media in postcommunism. This development consists of the strategic use of personalization, achieved through the talk show dispositive, for the enactment of positions of journalistic interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In modern talk shows, hosts apply different models of behaviour that vary from neutral to highly aggressive (Beciu et al, 2018;Fairclough, 1995;Vraga et al, 2012). Although research findings have demonstrated that the neutral hosting style performs 'the best for audiences' perception of credibility' (Vraga et al, 2012: 15), the role of a 'fair-minded moderator' (Ettema, 2007) is hardly suitable for propaganda aims.…”
Section: The Talk Show As a Propaganda Toolmentioning
confidence: 99%
“…In modern talk shows, hosts apply different models of behaviour that vary from neutral to highly aggressive (Beciu et al, 2018;Fairclough, 1995;Vraga et al, 2012). Although research findings have demonstrated that the neutral hosting style performs 'the best for audiences' perception of credibility' (Vraga et al, 2012: 15), the role of a 'fair-minded moderator' (Ettema, 2007) is hardly suitable for propaganda aims.…”
Section: The Talk Show As a Propaganda Toolmentioning
confidence: 99%